Wheat bran promotes enrichment within the human colonic microbiota of butyrate‐producing bacteria that release ferulic acid. (21st January 2016) - Duncan, Sylvia H.; Russell, Wendy R.; Quartieri, Andrea; Rossi, Maddalena; Parkhill, Julian; Walker, Alan W.; Flint, Harry J.
Summary: Cereal fibres such as wheat bran are considered to offer human health benefits via their impact on the intestinal microbiota. We show here by 16S rRNA gene‐based community analysis that providing amylase‐pretreated wheat bran as the sole added energy source to human intestinal microbial communities in anaerobic fermentors leads to the selective and progressive enrichment of a small number of bacterial species. In particular, OTUs corresponding to uncultured Lachnospiraceae (Firmicutes) related to E ubacterium xylanophilum and B utyrivibrio spp. were strongly enriched (by five to 160 fold) over 48 h in four independent experiments performed with different faecal inocula, while nine other Firmicutes OTUs showed > 5‐fold enrichment in at least one experiment. Ferulic acid was released from the wheat bran during degradation but was rapidly converted to phenylpropionic acid derivatives via hydrogenation, demethylation and dehydroxylation to give metabolites that are detected in human faecal samples. Pure culture work using bacterial isolates related to the enriched OTUs, including several butyrate‐producers, demonstrated that the strains caused substrate weight loss and released ferulic acid, but with limited further conversion. We conclude that breakdown of wheat bran involves specialist primary degraders while the conversion of released ferulic acid is likely to involve a multi‐species pathway.